5N-3(N-2)=N+3

Simple and best practice solution for 5N-3(N-2)=N+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5N-3(N-2)=N+3 equation:


Simplifying
5N + -3(N + -2) = N + 3

Reorder the terms:
5N + -3(-2 + N) = N + 3
5N + (-2 * -3 + N * -3) = N + 3
5N + (6 + -3N) = N + 3

Reorder the terms:
6 + 5N + -3N = N + 3

Combine like terms: 5N + -3N = 2N
6 + 2N = N + 3

Reorder the terms:
6 + 2N = 3 + N

Solving
6 + 2N = 3 + N

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '-1N' to each side of the equation.
6 + 2N + -1N = 3 + N + -1N

Combine like terms: 2N + -1N = 1N
6 + 1N = 3 + N + -1N

Combine like terms: N + -1N = 0
6 + 1N = 3 + 0
6 + 1N = 3

Add '-6' to each side of the equation.
6 + -6 + 1N = 3 + -6

Combine like terms: 6 + -6 = 0
0 + 1N = 3 + -6
1N = 3 + -6

Combine like terms: 3 + -6 = -3
1N = -3

Divide each side by '1'.
N = -3

Simplifying
N = -3

See similar equations:

| (3/4(x^2))-(3/2x)-(1/4)=0 | | 3(M-2)-2M=5 | | 2k(k+7)=2k^2+2(7)k | | 0.10x+0.05y=5.75 | | 5x+20=3x-20 | | 29x-50=22-2x | | 5x-9=82-8x | | 2(x-1)=3x-8 | | 7/8x-5/8=8 | | 3x^3-108=0 | | (x+2)(x+2)-3x-6=0 | | 4(n-5)=4 | | 26x+21=(-39x)-10 | | x+x+20+(210-3x)=180 | | 4.46x+8.92=17.84 | | 4.46+8.92=17.84 | | 15g+45=5[k-10] | | 15g+45=[k-10] | | (2+4)2= | | 3w-12=3w-12 | | y=10/17-x | | log(4)x+log(4)(x+12)=3 | | x^2+y^2+4x-10y=20 | | 4X-16=16X | | log(3)(2x+1)+log(3)(x+8)=3 | | p(x)=3x-5 | | Log(3)(3x+4)=2 | | Log(3)(3x+4)=-2 | | 4(x+1)(x+1)=2(x+1)(2x-3) | | (m-2)+(m-5)+(m-7)+2+6+5+7=m | | 3xsquare-5x+2=0 | | 2z^2-3=-z-2 |

Equations solver categories